Analisando a construção do espaço urbano em Manaus: PROSAMIM, uma vitrine para o capital? - (:unkn) unknown (Universidade Federal do Amazonas, 2019)
The processes of urbanization reflect, in addition to constructed forms and spaces produced, actors that are objectively configuring the city. Manaus, with 2.0 thousand inhabitants faces serious urban problems typical of capitalist big cities, marked by a process of rapid and disorderly urban growth. Historically, the lack of housing alternatives has resulted in the creation of informal settlements along the banks of the creeks, posing risks to the residents of these areas. In this context PROSAMIM appears, with the objective of solving the social, urban and environmental problems of the city. The resources for this program are approximately 900 million dollars (IDB loan and own resources). It is fundamental in this process to understand the role of the State, as a regulator of the use and occupation of urban land, using the legal mechanisms available to it, such as public policy. Therefore, it was proposed as a general objective: To analyze the process of urbanization of the city of Manaus, with emphasis on the role of the State in the housing area, from the Social and Environmental Program of the Manaus Igarapés; and how specific: Identify how the construction and occupation of the urban space of Manaus occurred and the State's performance in this process; To know the proposal of the Social and Environmental Program of the Igarapés of Manaus in its stages I, II and III and its contribution to the city and to unveil how PROSAMIM was implemented in its four axes: Social, Environmental, Territorial and Institutional, with focus in their priorities and relegation. The research modality used was the documentary, bibliographical and iconographic, using a critical-dialectic perspective, where through analysis of PROSAMIM documents, laws, decrees, reports, as well as reference works, theses and dissertations, scientific journals , annals of scientific meetings and periodical indexation and summary, among others, it was possible to investigate how the public policy of urbanization in the city was structured with emphasis on housing, and what the State intends with the implementation of PROSAMIM in Manaus. It can be affirmed that PROSAMIM is a program that comes to contribute with the layout of the city and the real estate valuation above any other proposed objective.
Keywords: Urbanização - Manaus (AM); Habitação - Manaus (AM); CIÊNCIAS SOCIAIS APLICADAS: SERVIÇO SOCIAL; Urbanização; Habitação; Estado; PROSAMIM